Metabolic Disturbances In The Patients With Acute Ischemic Stroke - Daniela Arabadzhieva; Ara Kaprelyan; Zhaneta Georgieva; Zdravko Slavov; Aleksandra Tsukeva (Journal of Biomedical & Clinical Research)
The purpose of this study was to analyze the disturbances of glucose, lipid and protein metabolism in acute ischemic stroke patients. A total of 258 patients (mean age 70.9±7.22 years, range 49-92 years) were studied. The following parameters were examined: blood glucose, triglycerides, total cholesterol, HDL-cholesterol, LDL-cholesterol, creatinine, and urea. Data were statistically processed by variation and correlation analysis. Our results demonstrated abnormal values of these laboratory parameters in most patients. The mean concentrations of triglycerides, total cholesterol and LDL-cholesterol were higher in females, while these of blood glucose were higher in males, especially in the age group between 76 and 80 years. Pearson’s correlation coefficient was highest between the variables ‘total cholesterol’ and ‘LDL-cholesterol’ (r=0.797) but moderate - between some of the rest variables such as ‘creatinine’ and ‘urea’ (r=0.575); ‘total cholesterol’ and ‘triglycerides’ (r=0.565); ‘total cholesterol’ and ‘urea’ (r=0.428); ‘triglycerides’ and ‘urea’ (r=0.370) and ‘LDL-cholesterol’ and ‘urea’ (r=0.301). In conclusion, the metabolic disorders are relatively common among acute ischemic stroke patients and play a specific role as risk factors for this disease. These parameters should regularly be controlled within the outpatient practice in order to warrant an effective prevention of acute ischemic stroke.